Magnetic multilayer hydrogel oral microrobots for digestive tract treatment - Xu, Ziheng; Wu, Zehao; Xu, Zichen; Xu, Qingsong (Frontiers in Robotics and AI, 2024)
Oral administration is a convenient drug delivery method in our daily lives. However, it remains a challenge to achieve precise target delivery and ensure the efficacy of medications in extreme environments within the digestive system with complex environments. This paper proposes an oral multilayer magnetic hydrogel microrobot for targeted delivery and on-demand release driven by a gradient magnetic field. The inner hydrogel shells enclose designated drugs and magnetic microparticles. The outer hydrogel shells enclose the inner hydrogel shells, magnetic microparticles, and pH neutralizers. The drug release procedure is remotely implemented layer-by-layer. When the required gradient magnetic field is applied, the outer hydrogel shells are destroyed to release their inclusions. The enclosed pH neutralizers scour the surrounding environment to avoid damaging drugs by the pH environment. Subsequently, the inner hydrogel shells are destroyed to release the drugs. A set of experiments are conducted to demonstrate the wirelessly controllable target delivery and release in a Petri dish and biological tissues. The results demonstrated attractive advantages of the reported microrobot in microcargo delivery with almost no loss, remote controllable release, and drug protection by the pH neutralizers. It is a promising approach to advance next-generation precision oral therapies in the digestive system.